Diagnostic performance of the GGT/HDL-C ratio for NAFLD in adults with obesity undergoing bariatric surgery - Pajuelo-Vasquez, Renzo (2024)
Background: Non-alcoholic fatty liver disease (NAFLD) has become the most frequent liver disease, closely related with metabolic risk factors such as obesity, insulin resistance, dyslipidemia, diabetes mellitus, and metabolic syndrome. In this context, γ-Glutamyl transpeptidase (GGT) and high-density lipoprotein cholesterol (HDL-C) have shown correlations with steatosis severity and metabolic syndrome, respectively. This positions the GGT/HDL-C ratio as a potential diagnostic indicator for NAFLD. Objective: To assess the diagnostic performance of the GGT/HDL-C ratio for NAFLD in adults with obesity undergoing bariatric surgery. Methods: We conducted an analytical cross-sectional study, designed as a diagnostic test evaluation. A secondary database of 249 adults with obesity was analyzed. The optimal cut-off point was ascertained using three methodologies, and five adjustment models were constructed for the total population, further stratified by sex. Results: The optimal cut-off point was 20.5 U/mmol and the AUC of the ratio was 0.81 (95% CI: 0.64–0.98), with sensitivity and specificity being 82.5% and 77.8%, respectively. In the overall group with an elevated GGT/HDL-C ratio, the prevalence of NAFLD increased by 14% (PR: 1.14; 95% CI: 1.04–1.33). Specifically, women displaying this altered ratio showed a 19% increased prevalence (PR: 1.19; 95% CI: 1.07–1.42) compared to those with normal values. Conclusions: The GGT/HDL-C ratio is a promising biomarker for the diagnosis of NAFLD in an adult population living with obesity.